Anabolic-androgenic steroids: Use and abuse in pediatric patients - Kerr, J. M.; Congeni, J. A. (Pediatric Clinics of North America, 2007)
The "win at all costs" mentality fuels athletes to seek performance-enhancing substances, such as anabolic-androgenic steroids, to gain an advantage over their opponents. Nonathletes espouse this same attitude to "win" the battle of attractiveness. An enhanced understanding of anabolic-androgenic steroids and the motivations behind their abuse will arm pediatricians with the ability to engage their patients in a balanced discussion of the benefits and costly risks of anabolic-androgenic steroids and successfully deter further use.